Prevalencia de ansiedad en estudiantes universitarios (2015)
College students are a risk group for anxiety for their psychological, social and academic demands, and high stress. In order to determine the prevalence of anxiety in students from a private university in Medellin and its association with socio-demographic and academics, a prevalence study with 200 students selected using stratified probability sampling was carried out. The anxiety screening was performed with the Zung scale. We assessed the reliability of the scale with Cronbach’s α, the analysis was performed using summary measures, frequencies, Mann Whitney’s U and chi square in SPSS 21®. The prevalence of anxiety was 58 %. The Zung scale showed excellent reliability with Cronbach’s α of 0.8. The prevalence of anxiety presented a statistically equal distribution by sex and age group, no association was found with the training cycle, academic program, age, credits or occupation. Anxiety was statistically lower in middle-class students. We found a high prevalence of anxiety, which highlights the need to develop educational strategies, identify high-risk students and initiate health interventions opportunely.